PREVALENCE OF ARTERIAL HYPERTENSION AND RISK FACTORS IN YOUNG ADULTS - N. T. Vatutin; E. V. Sklyanna (Архивъ внутренней медицины, 2017)
Arterial hypertension (AH) is one of the most widespread diseases in whole the world. AH in youth is associated with high cardiovascular mortality in middle age.Objectives: The study objectives were to studied prevalence of AH and risk factors in young adults.Methods. We studied prevalence of AH and risk factors in 981 young adults aged 20-29 years old (22,3 ± 2,26) in cross-sectional epidemiological study.Results. Prevalence of AH was 14,2%, it was significantly higher in men (22,2%) then in women (4,5%), p>0,05. There was a high prevalence of AH risk factors: overweight (35,4% in men), smoking (27,8% in men), parental hypertension (57,8%), noncompliance of day regimen (58,8%), high stress level (37,7%). In AH group prevalence of overweight, smoking, high salt consumption, parental hypertension and hypodinamia was significantly higher than in population.Conclusions. Prevalence of AH was 14,2%, main risk factors of AH were observed in more then quarter of studied persons.